2022
DOI: 10.1186/s13287-022-03050-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of mesenchymal stem cells and their exosomes in Parkinson’s disease treatment

Abstract: Parkinson's disease (PD) is the second most predominant neurodegenerative disease worldwide. It is recognized clinically by severe complications in motor function caused by progressive degeneration of dopaminergic neurons (DAn) and dopamine depletion. As the current standard of treatment is focused on alleviating symptoms through Levodopa, developing neuroprotective techniques is critical for adopting a more pathology-oriented therapeutic approach. Regenerative cell therapy has provided us with an unrivalled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 135 publications
1
34
0
Order By: Relevance
“…It was in accordance with some research exhibiting MSC‐exosomes improved cognitive deficits in Alzheimer's disease models by inhibiting pro‐inflammatory properties of microglia 130–132 . Concerning Parkinson's disease (PD), a growing number of studies have confirmed that MSC‐derived exosomes have considerable therapeutic benefits in PD 133–135 . Chen and colleagues investigated the possibility that experimental rats receiving intravenously administered MSC‐Exos may stimulate the repair and regeneration of damaged dopaminergic neuronal cells 136 .…”
Section: Mesenchymal Stem Cells and Msc‐derived Exosomes Regulate Neu...supporting
confidence: 71%
See 1 more Smart Citation
“…It was in accordance with some research exhibiting MSC‐exosomes improved cognitive deficits in Alzheimer's disease models by inhibiting pro‐inflammatory properties of microglia 130–132 . Concerning Parkinson's disease (PD), a growing number of studies have confirmed that MSC‐derived exosomes have considerable therapeutic benefits in PD 133–135 . Chen and colleagues investigated the possibility that experimental rats receiving intravenously administered MSC‐Exos may stimulate the repair and regeneration of damaged dopaminergic neuronal cells 136 .…”
Section: Mesenchymal Stem Cells and Msc‐derived Exosomes Regulate Neu...supporting
confidence: 71%
“…[130][131][132] Concerning Parkinson's disease (PD), a growing number of studies have confirmed that MSC-derived exosomes have considerable therapeutic benefits in PD. [133][134][135] Chen and colleagues investigated the possibility that experimental rats receiving intravenously administered MSC-Exos may stimulate the repair and regeneration of damaged dopaminergic neuronal cells. 136 MSC-exosomes readily crossed the BBB and entered the substantia nigra, resulting in a substantial decrease in neuronal death.…”
Section: Mesenchymal Stem Cells and Msc-derived Exosomes Regulate Neu...mentioning
confidence: 99%
“…When it comes to its treatment, MSCs have demonstrated significant potential in targeting the disease's pathogenesis through: 1) influencing the symptoms, 2) modifying the course of the disease, and 3) controlling disease manifestation (Table 2). A study by Boika et al confirmed that the transplantation of MSCs into PD patients decreased the severity of motor and non-motor symptoms (Boika et al, 2020), suggesting that MSCs are interesting potential candidates for disease-modifying strategies in PD (Vilaça-Faria et al, 2019;Berlet et al, 2022;Heris et al, 2022).…”
Section: Parkinson's Diseasementioning
confidence: 96%
“…These exosomes can cross the BBB and exert neuroprotective effects (D'angelo et al, 2020). As such, MSCs therapy in combination with Levodopa might be the future standard of PD treatment (Heris et al, 2022). Some application of MSCs for treatment of PD have also entered clinical trials to compare their efficacy (Identifiers: NCT03550183, NCT01446614, NCT02611167, NCT04506073, NCT03684122, NCT04146519, NCT04928287, NCT04876326 and NCT04995081) (Liu et al, 2022b).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are regarded to be very promising in treating PD, as they can differentiate into dopaminergic neurons and produce neurotrophic substances. The precise process by which stem cells repair neuronal injury is unknown, and MSC-derived exosomes are suggested to be responsible for a significant portion of such effects [ 417 , 418 ]. Moreover, using three transcription factors (NEUROD1, LMX1A, and ASCL1), miR218 and collectively designated NeAL218, DA neurons are generated by directly reprogramming human astrocytes in vitro and mouse astrocytes in vivo [ 419 ].…”
Section: Treatment and Optimization Of The Condition Of Patients With Pdmentioning
confidence: 99%